Análise dos artigos da revista eletrônica ensino, saúde e ambiente que versem sobre “ambiente; ambiental; meio ambiente; e/ou educação ambiental” - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The present work is an exploratory research of qualitative quantitative nature, which compose a critical analysis of the productions and objectives related to the articles published in the Journal Teaching, Health and Environment. These included the word "environment" and its derivations, published from the year of its first publication, in 2008, until the 2016 edition, in order to contribute to the evaluation of the scientific production on this subject. For this, qualitative data collection was performed through content analysis and the quantitative data were obtained by scientometric analysis. From the results related to the area of knowledge, it was possible to perceive three broad areas of coverage: "environmental education", "promotion and conservation of the environment", "health and environment relationship". Regarding the places of development of the publications, the formal spaces of education are evidenced, followed by the texts of revision and the works directed to the environments and / or agents promoters of health. With regard to the objectives presented in the publications, the most expressive categories were those that sought strategies for teaching methodologies or mapping of scientific production in the area. It was concluded that the methodology of analysis was adequate to the research proposed in the paper, demonstrating the tendency of the publications and the contribution of the publication of the journal to the diffusion of science. Finally, it is important to emphasize the importance of developing studies to analyze the scientific production, in order to verify trends and identify possible gaps, serving as a resource to guide researchers on the choice of topics in future research.
Analysis of the articles in the electronic journal education, health and environment that deal with “environment; environment; environment; and / or environmental education ”
Keywords: Ciências da natureza; Ambiente; Análise crítica; Análise cientométrica; Produção científica; Environment; Critical analysis; Scientific analysis; Scientific production; Natural sciences; Cientométrica; CNPQ::CIENCIAS EXATAS E DA TERRA